18F-ASEM Imaging for Evaluating Atherosclerotic Plaques Linked to α7-Nicotinic Acetylcholine Receptor - Yang, Tao; Wang, Dawei; Chen, Xiangyi; Liang, Yingkui; Guo, Feng; Wu, Chunxiao; Jia, Liujun; Hou, Zhihui; Li, Wenliang; He, ZuoXiang; Wang, Xin (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Atherosclerosis is a chronic vascular inflammatory procedure alongside with lipid efflux disorder and foam cell formation. 7-nicotinic acetylcholine receptor (α7nAChR) is a gated-calcium transmembrane channel widely expressed in neuron and non-neuron cells，such as monocytes and macrophages, activated-T cells, dendritic cells and mast cells. 18F-ASEM is an inhibitor targeted to α7nAChR that had been successfully applied in nervous system diseases. Previous studies had highlighted that α7nAChR was related to the emergency of vulnerable atherosclerotic plaques with excess inflammation cells. Thus ,18F-ASEM could be a complementary diagnostic approach to atherosclerotic plaques. Materials and Methods: The synthesis of ASEM precursor and 18F-labeling had been performed successfully. We had established the ApoE-/-mice atherosclerotic plaques model (fed with western diet) and New Zealand rabbits atherosclerotic models (balloon-sprained experiment and western diet.)After damage of endothelial cells and primary plaque formation, 18F-ASEM imaging of atherosclerotic plaques linked to α7nAChR had been conducted. In vivo micro-PET/CT imaging of ApoE-/-mice and control group were performed 1h after injection of 18F-ASEM (100-150 μCi), PET/CT imaging for rabbits with atherosclerotic plaques and control ones was also performed. Meanwhile, we also conducted CT-scan on the abdominal aorta of these rabbits. After that, the animals were sacrificed, the carotid and abdominal aorta were separately taken out for circular sections. The paraffin embedded specimens were sectioned with 5μm thickness and stained with hematoxylin-eosin (H&E) and oil red. Results: In vivo vessel binding of 18F-ASEM and α7nAChR expression in model group with atherosclerosis plaques was significantly higher than in control group. PET/CT imaging successfully identified the atherosclerotic plaques in ApoE-/-mice and model rabbits; whereas, no obvious signals were detected in normal mice or rabbits. Compared with 18F-FDG, 18F-ASEM had more significant effect on the early monitoring of inflammation in carotid atherosclerotic plaques of ApoE-/-mice and model rabbits. 18F-ASEM had relatively more palpable effect on the imaging of abdominal aorta with atherosclerosis in rabbits. H&E and oil red staining identified the formation of atherosclerotic plaques in model animals, which provided pathological basis for the evaluation of imaging effects. Conclusion: We firstly confirmed 18F-ASEM as radiotracer with good imaging properties for precise identification of atherosclerotic diseases.